2017
DOI: 10.1002/jso.24620
|View full text |Cite
|
Sign up to set email alerts
|

The SORG nomogram accurately predicts 3‐ and 12‐months survival for operable spine metastatic disease: External validation

Abstract: The SORG nomogram accurately estimated 3- and 12-months survival for operable spine metastatic disease, and is therefore, useful in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…[17] The SORG nomogram also performed very well in our international cohort with an AUC of 0.87 for 90-days and 0.76 for 1-year. These findings are even more encouraging when compared with the results from Nater et al [10] that showed an AUC of 70 for 3-months and 0.78 for 12-months for the best predictive tool among nine different scoring systems or even from Paulino Pereira and Bongers et al [20,18] These facts also mean that this study is the first to show a clear advantage of the SORG at one year, compared with the Tokuhashi.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[17] The SORG nomogram also performed very well in our international cohort with an AUC of 0.87 for 90-days and 0.76 for 1-year. These findings are even more encouraging when compared with the results from Nater et al [10] that showed an AUC of 70 for 3-months and 0.78 for 12-months for the best predictive tool among nine different scoring systems or even from Paulino Pereira and Bongers et al [20,18] These facts also mean that this study is the first to show a clear advantage of the SORG at one year, compared with the Tokuhashi.…”
Section: Discussionsupporting
confidence: 73%
“…Our hypothesis is that, as partially demonstrated previously, [16,20,18,19] the SORG nomogram and ML are better predictive tools than the Tokuhashi Original or Revised scores for spinal metastatic disease survival at 3 months and 1 year. This international validation followed the Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis (TRIPOD).…”
Section: Methodsmentioning
confidence: 53%
“…Furthermore, well established scoring systems such as the Bauer, 35 New England Spinal Metatasis, 36 Katagiri, 37 Sioutos, 7 SORG, 38 Tokuhashi, 39 Tomita, 40 van der Linden 41 and others 6 , 42 currently incorporate measures of preoperative metastatic tumour burden by assessing the number of spine metastasis, other non-spine bone metastasis and visceral metastasis. However, despite controlling for these and other factors, serum alkaline phosphatase remained an independent prognostic factor on multivariable analysis; in addition, visceral metastasis no longer reached significance after incorporation of serum alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…The SORG nomogram has demonstrated great accuracy in estimating survival at 3 months and 12 months for patients with operable spinal metastasis. 56 Its accuracy in predicting 3-, 6- and 12-month survival was 90%, 71% and 78%, respectively. 56 It is also amongst the limited scores showing good discriminative ability, consistently displaying an area under curve above 0.70 in receiver operating characteristic analysis for various time frames.…”
Section: Survival Predictionmentioning
confidence: 96%
“…The Skeletal Oncology Research Group (SORG) nomogram is a model composed of age, primary tumour type, Eastern Cooperative Oncology Group (ECOG) performance scale, presence of brain/visceral metastasis, number of spinal metastases, laboratory markers (white blood cell count and haemoglobin) and previous systemic treatment. 56 The risk magnitude of each factor is weighted from the value individually measured in the specific evaluated patient. The SORG nomogram has demonstrated great accuracy in estimating survival at 3 months and 12 months for patients with operable spinal metastasis.…”
Section: Survival Predictionmentioning
confidence: 99%